2020
DOI: 10.1111/nrm.12254
|View full text |Cite
|
Sign up to set email alerts
|

Observed and projected trends of extreme precipitation and maximum temperature during 1992–2100 in Isfahan province, Iran using REMO model and copula theory

Abstract: Meteorological extreme events have a major impact on water resources, economic development, and ecosystem health. In this study, maximum precipitation and maximum temperature indices were derived for Isfahan province, in central Iran, over the historical and future (2020-2100) periods. Precipitation and maximum temperature data from the REMO model under RCP4.5 scenario were used to investigate changes in extreme values over the future period. The results showed that extreme precipitation in the historical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Copulas were also used in a few studies considering bias correction of temperature and precipitation data, each variable was corrected separately but at different locations (e.g., Alidoost et al, 2017;Lazoglou and Anagnostopoulou, 2019). In addition to bias correction, copulas in climatology are used to investigate trends in extreme precipitation and temperature, as in Mirakbari et al (2020). In the work by Laux et al (2011), the focus was on the positive pairs of observed and modelled precipitation, and with the usage of empirical copulas, statistical downscaling of precipitation over the complex terrain in the Alpine region of Germany was performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copulas were also used in a few studies considering bias correction of temperature and precipitation data, each variable was corrected separately but at different locations (e.g., Alidoost et al, 2017;Lazoglou and Anagnostopoulou, 2019). In addition to bias correction, copulas in climatology are used to investigate trends in extreme precipitation and temperature, as in Mirakbari et al (2020). In the work by Laux et al (2011), the focus was on the positive pairs of observed and modelled precipitation, and with the usage of empirical copulas, statistical downscaling of precipitation over the complex terrain in the Alpine region of Germany was performed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to bias correction, copulas in climatology are used to investigate trends in extreme precipitation and temperature, as in Mirakbari et al . (2020). In the work by Laux et al .…”
Section: Introductionmentioning
confidence: 99%